Assessment and bioremediation of mercury pollutants by highly mercury-resistant bacteria immobilized in biochar from small-scale artisanal gold mining areas - Dewi Nursaidah Rohmah; Endah Retnaningrum (Brawijaya University, 2023)
Small-scale gold mining activities in Indonesia still use amalgamation techniques, which have the potential to cause mercury (Hg) pollution and affect the quality and number of microorganisms. Mercury-resistant bacteria can survive and adapt to mercury-exposed environments and can be developed as bioremediation agents. The bioremediation activity of these bacteria can be increased through immobilization using biochar. The results of observations of physicochemical qualities in three samples in the mining area, showed significant differences. The TOC in the rhizosphere soil sample of Calliandra calothyrsus L. showed the significantly highest value at 14.5%, and the pH of the three samples indicated acidity and exhibited no difference (p<0.05). The highest concentration measured in the tailing sample was 9.9 ng/g (p<0.05). The number of heterotrophic bacteria in the rhizosphere soil was the highest at 7.2 × 108 CFU/g. On the other hand, the number of mercury-resistant bacteria in the tailing sample showed the highest value of 6.3 × 103 CFU/g. In the selection based on the toxicity profile of 30 mercury-resistant bacteria obtained, the highest results were observed in the LMP1B5 bacterial isolate from the river sediment, with 50% effective concentration (EC50) and minimum inhibitory concentration (MIC) values of 225 and 250 mg/L, respectively. Polyphasic identification based on phenotypic and genotypic characteristics using the 16S rRNA gene showed that the bacterial isolate was identified as Escherichia fergusonii. The growth and mercury removal activity of E. fergusonii LMP1B5 increased by 21% and 52%, respectively, after the immobilization with biochar. Thus, immobilized E. fergusonii LMP1B5 was effective in removing mercury pollutants.